Pharmacotherapeutic Determinants for QTc Interval Prolongation in Japanese Patients with Mood Disorder - Okayasu, H.; Ozeki, Y.; Fujii, K.; Takano, Y.; Saeki, Y.; Hori, H.; Horie, M.; Higuchi, T.; Kunugi, H.; Shimoda, K. (Pharmacopsychiatry, 2012)
An increased incidence of sudden death has been observed among patients treated with antidepressants. A prolonged QTc interval is a known prognostic factor for fatal arrhythmia, and several studies have shown that the use of antidepressants can cause a prolonged QTc interval. However, few studies, especially in Japan, have compared the effects of multiple drugs on QTc interval or examined dose relationships in a clinical setting.We compared the effects of antidepressants on QT interval, corrected to QTc by Bazett's formula, in 729 Japanese patients who were diagnosed with mood disorder.Using stepwise multiple linear regression analysis, we found that the use of tricyclic antidepressants (P<0.01) and concomitant use of antipsychotics (P<0.05), as well as advanced age and being female (known factors for prolonged QTc interval; both P<0.01), significantly prolonged the QTc interval. Analysis of individual antidepressants also revealed that the use of clomipramine (P<0.01) and amitriptyline (P<0.05) significantly prolonged the QTc interval.Our results reveal that tricyclic antidepressants, especially clomipramine and amitriptyline, confer a risk of prolonged QTc interval in a dose-dependent manner. The selective serotonin reuptake inhibitors investigated (fluvoxamine, paroxetine, sertraline) were not indicated as risk factors for QTc prolongation.
Keywords: antidepressants; QTc interval; sudden death; tricyclic antidepressants; selective serotonine reuptake inhibitors